MODERN APPROACHES TO PREMATURE TERMINATION (MEDICAMENTOUS METHOD) - Gulammaxmudova, D.V.; Samatova , Y.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This review explores current trends aimed at improving the quality of women’s healthcare in cases of early abortion. It highlights the expansion of medical indications and the extended time frame for performing abortions during the first trimester. The discussion also encompasses the clinical approaches to managing incomplete abortions, whether spontaneous or medically induced, as well as uterine evacuation protocols in cases of missed miscarriage and strategies for terminating pregnancies in later stages. The author emphasizes that pharmacological termination methods in early gestation provide notable benefits and may ultimately supersede surgical procedures.